2022
DOI: 10.3390/ani12111435
|View full text |Cite
|
Sign up to set email alerts
|

Copy Number Variation (CNV): A New Genomic Insight in Horses

Abstract: Copy number variations (CNVs) are a new-fangled source of genetic variation that can explain changes in the phenotypes in complex traits and diseases. In recent years, their study has increased in many livestock populations. However, the study and characterization of CNVs in equines is still very limited. Our study aimed to investigate the distribution pattern of CNVs, characterize CNV regions (CNVRs), and identify the biological pathways affected by CNVRs in the Pura Raza Española (PRE) breed. To achieve this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 55 publications
(132 reference statements)
2
8
0
Order By: Relevance
“…To identify genes that may be influenced by CNVRs within the genome, an annotation analysis of genes associated with CNVRs revealed that olfactory-related functions, specifically olfactory transduction and olfactory receptor activity, were frequently affected. This observation aligns with previous findings in various species, including cattle ( 119 ), sheep ( 62 , 111 ), horses ( 34 , 115 , 120 ) and humans ( 121 123 ), where genes affected by copy number variation have shown enrichment for olfactory-related functions. In the case of humans, the sense of smell is considered a minor aspect of overall health and may not be closely linked with adaptation.…”
Section: Gene Ontology Analysis For Genes Overlapping Cnvrssupporting
confidence: 92%
See 1 more Smart Citation
“…To identify genes that may be influenced by CNVRs within the genome, an annotation analysis of genes associated with CNVRs revealed that olfactory-related functions, specifically olfactory transduction and olfactory receptor activity, were frequently affected. This observation aligns with previous findings in various species, including cattle ( 119 ), sheep ( 62 , 111 ), horses ( 34 , 115 , 120 ) and humans ( 121 123 ), where genes affected by copy number variation have shown enrichment for olfactory-related functions. In the case of humans, the sense of smell is considered a minor aspect of overall health and may not be closely linked with adaptation.…”
Section: Gene Ontology Analysis For Genes Overlapping Cnvrssupporting
confidence: 92%
“…Furthermore, they constructed an autosomal map of CNVRs in horses. In addition, Laseca et al ( 34 ) analyzed high-density SNP genotyping data from 654 horses, identifying a total of 19,902 CNV segments and 1,007 CNV regions, with CNVs covering 4.4% of the equine genome.…”
Section: Overview Of Screening Methods For Cnvs In Herbivorous Livest...mentioning
confidence: 99%
“…To characterize the CNVRs identified in this study in more detail, we compared them to those identified in ten previous studies that used various methods [ 13 , 15 , 33 , 34 , 35 , 38 , 39 , 40 , 41 , 42 ]. A total of 2519 CNVRs were identified across all 11 studies: 1844 (73.2%) CNVRs were identified in our study and the previous studies, and 675 (26.8%) CNVRs were identified only in this study ( Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Doan et al (2012) published the first study to detect genome-wide CNVs in horses, using a whole-exome tiling array and an array-comparative genomic hybridization platform. Since the development of high-density SNP arrays for horses [ 7 , 11 ], CNVs could be also assessed throughout the genomes of various horse breeds, of which some studies investigated potential associations with traits of interest in horses, including body size and genetic risk factors for insect-bite hypersensitivity [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several CNV-overlapping candidate genes were discovered to be associated with thermal adaptation in Jinjiang horses ( 12 ). Recent CNV survey studies utilized European horse breeds ( 13 ), Criollo Argentino horses ( 14 ), South Korean horse breeds ( 15 ), and purebred Spanish horses ( 16 ). However, all of these studies mentioned above were conducted either using PCRs, microarrays, or SNP chips and to our best knowledge, only a few studies were conducted using whole-genome sequencing to detect CNVs in horse populations ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%